PELATIHAN METODE PEMBELAJARAN BAHASA ASING (ARAB & INGGRIS) BAGI GURU (ASATIDZ DAN UMMAHAT) DI PESANTREN TERPADU SERAMBI MEKKAH KOTA PADANG PANJANG - HB, Zulfahmi; Zalnur, Muhammad; Basit, Abdul (Jurnal Abdimas Bina Bangsa, 2024)
The application of learning methods will not work effectively if their application is not based on adequate knowledge. A method can be an obstacle to the learning process, not a component that supports the achievement of goals. Improving the quality of teachers is something that must be done by the education unit. The Serambi Mekkah Integrated Islamic Boarding School took the initiative to improve the skills of teachers (asatidz and ummahat) in learning, especially learning foreign languages, namely Arabic and English. The purpose of this activity is to increase the quality of language learning and so that the mastery of foreign languages and the communication skills of the students of the Serambi Mekkah Integrated Islamic Boarding School are also growing. The method of this activity uses the lecture method, direct demonstrations are practiced by participants, and questions and answers. The lecture method is used to convey general knowledge about the concept of language learning methods, grammar and translation methods (Qowaid wa tarjamah), direct method (mubasyarah), audiolingual method / sam'iyyah safahiyyah. Demonstrations are used to provide hands-on skills regarding the process of applying learning methods. Questions and answers are used to complete things that have not been accommodated by the two methods above. The results of this training can be declared successful. This can be seen from: (1) The attendance of participants is in accordance with the target of 95% (27 of 30 participants) (2) the results of the training are stated to be very good according to the analysis of the performance appraisal rubric. (3) Participants are very enthusiastic about participating in the training, which can be seen from the seriousness of participating in the training, the many questions that arise in the mentoring process and the teacher's willingness to apply learning methods in foreign development, both Arabic and English.